Tangible cultural heritage conservation in reflecting the city image: the case study of Jonker Street and Heeren Street, Melaka - Musa, Shafiqah Musbar; Abu Bakar, Aniza (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
This study on the tangible cultural heritage of the Dutch, Baba Nyonya and Chinese was conducted at the Heeren Street and Jonker Street, focuses on whether the elements of architecture buildings, landscape, street lifestyle and economy practiced by the people are recognisable by the tourists.These also reflects the successions of the identity of these two streets. Cultural heritage is the reflection of identity of a particular group of people that are inherited from the past ascendants to their descendants. It is a reflection of the culture and the people’s way of life that later created the identity of the place. Without a proper conservation implied on these heritage values, the people of that particular area will lose their sense of belonging and the identity of their genus loci altogether. Hence a proper conservation will help the people of the place to keep be reminded of their origins and history from the past. Other than that, a good conservation of cultural heritage area would help the outsiders to easily identify the characteristics and identity of the place even without literal explanatory. Bandar Melaka, as one of the oldest city in Malaysia possesses a number of historical and heritage values all around it. As one of the World Heritage Sites declared by the UNESCO, this tourist attraction city is like a storyteller that tells the story of the place throughout time, from the past until now through the heritage values it possess. It has been determined that conservation projects applied in regard to heritage values of Jonker Street and Heeren Street was successful in significantly reflecting the influences of Dutch, Baba Nyonya and Chinese.